Review of Oliveirania santa catharinae (sic) Maury 1927 and associated ichnofossils (Itararé Group, Late Carboniferous of Paraná Basin, Brazil) (Terr@ Plural, 2021)
The sedimentary layers of Anitápolis, Santa Catarina, were the subject of relevant discussions about age and paleoenvironment in the first half of the 20th century. Today they are correlated to the ritmites from Itararé Group, but some of the fossils that are part of these studies were not subsequently revised. This is the case of Oliveirania santa catharinae (sic) Maury 1927, a species originally attributed to annelids, and the ichnofossils attributed to it by association. The Annelida fossils were considered here as pseudofossils of inorganic origin. The ichnofossils attributed to Oliveirania were redescribed as a new ichnospecies, Pterichnus mauryae isp. nov., possibly related to the activity of crustaceans. This is the first occurrence of Pterichnus in Brazil and the oldest in the world.
Keywords: Pterichnus mauryae isp. nov..; Rio do Sul Formation; Annelidae; Crustacea; Paleozoic